Menginspirasi Generasi Muda: Pendekatan Kreatif Dalam Pembelajaran Pendidikan Agama Islam - Lucky Zakwan; Muhammad Faris Marzuki; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
Islamic religious education is an important key in shaping the religious understanding and practices of the younger generation. However, traditional approaches to religious teaching are often unable to capture the interest and involvement of the younger generation who continue to grow in this digital era. Therefore, this article proposes a creative approach to Islamic learning to inspire the younger generation. This creative approach involves the use of various media, such as information technology, visual arts, music, and interactive games, to enrich their learning experience. For example, the use of mobile applications to guide them in carrying out daily worship, or the use of visual art and music to depict Islamic values in a contemporary context that is relevant to their lives. Apart from that, this approach also emphasizes active participation and deep understanding. through group discussions, role simulations, and collaborative projects. By providing opportunities for the younger generation to explore and reflect on Islamic values in an environment that supports creativity and exploration, it is hoped that they can strengthen their religious identity while remaining engaged and relevant in the modern world. Through a creative approach to learning about the Islamic religion, we can open the door for the younger generation to discover the depth and beauty of religious teachings, while still adapting to the demands of the times. In this way, we not only teach religion, but also foster enthusiasm, leadership and courage for future generations.